2020
DOI: 10.3390/ani10030420
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of miRNA-mRNA Network Reveals Different Regulatory Patterns in the Endometrium of Meishan and Duroc Sows during Mid-Late Gestation

Abstract: Embryo loss is a major factor affecting profitability in the pig industry. Embryonic mortality occurs during peri-implantation and mid-late gestation in pigs. Previous investigations have shown that the embryo loss rate in Meishan pigs is significantly lower than in commercial breeds. Most studies have focused on embryonic mortality during early gestation, but little is known about losses during mid-late gestation. In this study, we performed a transcriptome analysis of endometrial tissue in mid-late gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…We detected 403 known mature miRNAs among the six libraries using RNA-seq, which is a higher number than the previously reported numbers of miRNAs detected in porcine adipose tissue by RNA-seq (namely, 172 [27], 222 [28], 227 [15], 239 [14], 283 [12], and 309 [16]), but lower than the number (409) obtained by Davoli et al [17]. Although miRBase does have some weaknesses, it has been used widely for identifying porcine miRNA and is a popular and reliable platform for miRNA researches [16,17,29,30]. Although MiRgeneDB (https://mirgenedb.org/) [31] and miRCarta (https://mircarta.cs.uni-saarland.de/) [32] provide more accurate and reliable miRNA annotations, miRNAs from porcine species are not included in the current MiRgeneDB.…”
Section: Discussionmentioning
confidence: 64%
“…We detected 403 known mature miRNAs among the six libraries using RNA-seq, which is a higher number than the previously reported numbers of miRNAs detected in porcine adipose tissue by RNA-seq (namely, 172 [27], 222 [28], 227 [15], 239 [14], 283 [12], and 309 [16]), but lower than the number (409) obtained by Davoli et al [17]. Although miRBase does have some weaknesses, it has been used widely for identifying porcine miRNA and is a popular and reliable platform for miRNA researches [16,17,29,30]. Although MiRgeneDB (https://mirgenedb.org/) [31] and miRCarta (https://mircarta.cs.uni-saarland.de/) [32] provide more accurate and reliable miRNA annotations, miRNAs from porcine species are not included in the current MiRgeneDB.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have shown that miR-365-5p can target RNA-binding protein with serine-rich domain 1 ( RNPS1) , Keratin 14 ( KRT14) , and DnaJ heat shock protein family (Hsp40) member B6 ( DNAJB6) in porcine Alveolar Macrophages, thereby affecting interferon-mediated immune response [ 42 ]. Previous studies have shown that the differentially expressed miR-671-5p in the endometrium of Meishan and Duroc sows affects maternal placental development by targeting the Estrogen Receptor 1 ( ESR1) gene [ 5 , 43 ]. Among the genes targeted by the above miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of adjustment and coordination all contribute to spontaneous embryo loss. Insufficient blood supply to the uterus has been demonstrated to cause spontaneous embryo loss [ 3 , 4 , 5 , 6 , 7 ]. Previous studies found that vascular endothelium growth factors, hypoxia-inducible factor 1-α, IFN-γ, etc., all affect the angiogenesis between mother and fetus, ultimately leading to healthy and arresting embryos [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular biological mechanism of TFI is still unclear (Malogajski et al, 2019). Meanwhile, embryo implantation requires a precise synchronism between the receptive uterus (during the implantation window) and activated blastocyst (Abbas et al, 2020;Yang et al, 2020). Therefore, an in-depth study of the key genes and mechanisms of endometrium during the implantation window period in patients with TFI is of great significance for the pregnancy of TFI.…”
Section: Discussionmentioning
confidence: 99%